Sulfated Metabolites of Luteolin, Myricetin, and Ampelopsin: Chemoenzymatic Preparation and Biophysical Properties - Káňová, Kristýna; Petrásková, Lucie; Pelantová, Helena; Rybková, Zuzana; Malachová, Kateřina; Cvačka, Josef; Křen, Vladimír; Valentová, Kateřina (Journal of agricultural and food chemistry, 2020)
Authentic standards of food flavonoids are important for human metabolic studies. Their isolation from biological materials is impracticable; however, they can be prepared in vitro. Twelve sulfated metabolites of luteolin, myricetin, and ampelopsin were obtained with arylsulfotransferase from Desulfitobacterium hafniense and fully characterized by high-performance liquid chromatography, MS, and NMR. The compounds were tested for their ability to scavenge 1,1-diphenyl-2-picrylhydrazyl, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid), and N,N-dimethyl-p-phenylenediamine radicals, to reduce ferric ions and Folin-Ciocalteu reagent, and to inhibit tert-butyl hydroperoxide-induced lipid peroxidation of rat liver microsomes. The activity differed considerably even between monosulfate isomers. The parent compounds and myricetin-3'-O-sulfate were the most active while other compounds displayed significantly lower activity, particularly luteolin sulfates. No mutagenic activity of the parent compounds and their main metabolites was observed; only myricetin showed minor pro-mutagenicity. The prepared sulfated metabolites are now available as authentic standards for future in vitro and in vivo metabolic studies.
Keywords: Microsomes, Liver; quercetin; Desulfitobacterium; Rats; isomerie; Antioxidants; arylsulfotransferasa; Arylsulfotransferase; luteolin; Biophysical Phenomena; arylsulfotransferase; mužské pohlaví; biofyzikální jevy; ampelopsin; Lipid Peroxidation; krysa rodu Rattus; flavonoidy; antioxidancia; Bacterial Proteins; myricetin; Flavonoids; Luteolin; zvířata; biokatalýza; Biocatalysis; molekulární struktura; sulfates; jaterní mikrozomy; Sulfates; sírany; Isomerism; bakteriální proteiny; peroxidace lipidů; Male; Molecular Structure; Animals